Study on the knowledge, attitude and practice of single photon emission computed tomography among oncology healthcare professionals - Yan, Min; Cheng, Xiang; Li, Xinyu; Jin, Xiangting; Dai, Ying; Li, Fanfan (Frontiers in Public Health, 2024)
BackgroundSingle photon emission computed tomography (SPECT) is becoming increasingly popular in oncology. This study endeavors to scrutinize the radiation protection knowledge, attitude, and practice (KAP) exhibited by healthcare professionals involved in this imaging modality.MethodsThis cross-sectional study was conducted between September 23, 2023, and October 23, 2023, at the Second Affiliated Hospital of Anhui Medical University, the First Affiliated Hospital of Anhui Medical University, and the People’s Hospital of Liuan. Demographic data and KAP scores were acquired through the administration of questionnaires.ResultsA total of 450 healthcare professionals participated in the study. Correlation analyses revealed significant positive correlations between knowledge and attitude, knowledge and practice, as well as attitude and practice. Multivariate analysis indicated that being over 40 years old was independently associated with good knowledge, as well as positive attitudes. Occupations as nurses and having no contact with SPECT patients were independently associated with a lower level of knowledge, as well as negative attitudes. Furthermore, being female, having an occupation as a nurse, and not having received relevant training were independently associated with negative practice.ConclusionOncology healthcare professionals had suboptimal knowledge, negative attitude and inactive practice towards radiation protection in SPECT.